Status and Educational Attainment as Predictors of School Principals’ Competencies in the Philippine Public Schools - Kintanar, Gemma N. (JPAIR Institutional Research, 2017)
Principals play the role as leaders of school management and are responsible for the outcome of the school. The essential focus of this study is to assess the level of the core competencies of principals in public elementary and secondary schools in Kidapawan City Division, Philippines, for the academic year 2015-2016. A descriptive correlation design was used and treated the level of significance using regression analysis. Findings showed that the level of principal ’s competencies as perceived by themselves and teachers was PROFICIENT. The assessment on the level of principals ’ core competencies does not differ significantly between self and that of the teachers according to the context of the principal/school, technical and managerial capability, strategic management, inter and intrapersonal relationship and as the link to the community. The combined contribution of the principal ’s socio-demographics does not significantly influence their level of core competencies. Status stood out as a significant predictor of technical and managerial ability. Results revealed that the best predictor of the competency on academic leadership and coaching is educational attainment. The study concludes that the level of core competence of principals could contribute to underperforming schools. It is alarming to note that the principals lack a continuing professional development.